2023
DOI: 10.3390/pharmaceutics15010212
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Potential of Natural Compounds in Neurodegenerative Diseases: Insights from Clinical Trials

Abstract: Neurodegenerative diseases are caused by the gradual loss of neurons’ function. These neurological illnesses remain incurable, and current medicines only alleviate the symptoms. Given the social and economic burden caused by the rising frequency of neurodegenerative diseases, there is an urgent need for the development of appropriate therapeutics. Natural compounds are gaining popularity as alternatives to synthetic drugs due to their neuroprotective properties and higher biocompatibility. While natural compou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 129 publications
0
8
0
Order By: Relevance
“…One of the major criticisms made by the scientific community to the concept of nutraceuticals (i.e., the use of substances of natural origin as possible drugs) lies in the fact that despite the encouraged in vitro and in vivo outcomes when translated to clinical trials, Res did not show the expected significant therapeutic effects [ 16 ]. Res is subjected to intense metabolism by the enzymes present in the intestinal microbiota, on the intestinal epithelium, and in the liver, which considerably reduces its bioavailability and increases the concentration of its glucuronidated or sulfated metabolites, whose effects are currently unknown [ 43 , 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the major criticisms made by the scientific community to the concept of nutraceuticals (i.e., the use of substances of natural origin as possible drugs) lies in the fact that despite the encouraged in vitro and in vivo outcomes when translated to clinical trials, Res did not show the expected significant therapeutic effects [ 16 ]. Res is subjected to intense metabolism by the enzymes present in the intestinal microbiota, on the intestinal epithelium, and in the liver, which considerably reduces its bioavailability and increases the concentration of its glucuronidated or sulfated metabolites, whose effects are currently unknown [ 43 , 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Experiments conducted in neuronal-derived cell lines have also shown that Res treatment prevents rotenone-induced fragmentation of mitochondria by inducing mitochondrial fission and fusion and promoting ATP synthesis [ 15 ]. Unfortunately, Res use in clinics encounters several limitations [ 16 ]. In particular, the in vivo effects of Res appear to be affected by its low solubility, high biotransformation, and low bioavailability [ 17 , 18 , 19 ], which leads to the co-presence of a plethora of metabolites that could also exert effects that differ from the precursor and potentially impair its action, as demonstrated for the daidzein metabolites [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although there are currently approved drugs for NDs, the majority of them are used primarily to alleviate symptoms 4 . Due to their effectiveness in treating NDs, as well as their lower toxicity, natural compounds have attracted the attention of research groups around the world 5 . In order to highlight some promising natural compounds against neurodegeneration and its symptoms, the present review focused on the latest findings of phenolic compounds in the preclinical stage.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, the drugs that reach the lesion site might be recognized as “exogenous substances” by the immune system and removed (C. Guo, Cao, et al, 2023; R. Liu, Dong, et al, 2023), or their accumulation at the lesion site may be reduced due to lymphatic recirculation (A. Rajput et al, 2021; Yáñez et al, 2011). Because of these issues, many drugs developed from natural products fail to pass the clinical trial phase (Andrade et al, 2023; Mthiyane et al, 2022).…”
Section: Introductionmentioning
confidence: 99%